Enumerative Encoding of TMTR Codes for Optical Recording Channel. (26th September 2010) - Tsai, Hui-Feng
Abstract : We propose a new time-varying maximum transition run (TMTR) code for DVD recording systems, which has a rate8 / 11 higher than the EFMPlus code and a lower power spectral density (PSD) at low frequencies. An enumeration method for constructing the new TMTR code is presented. Computer simulations indicate that the proposed TMTR code outperforms the EFMPlus code in error performance when applied to partial response optical recording channels.